Faktor Yang Berhubungan Dengan Stres Kerja Pada Perawat di Ruang Rawat Inap RSUD Lasinrang - Gaziyyah, Fikriyah; Sartika; Ayu Puspitasari (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Stress is a non-specific response of the body to any demands or burdens given. Stress can arise when a person experiences a heavy burden or task and cannot cope with the assigned task. This study aims to determine the factors related to work stress in nurses in the inpatient ward installation at the Lasinrang Regional General Hospital, Pinrang Regency, in 2024. This study uses a quantitative research method with a cross-sectional research design. Sampling in this study was simple random sampling with a sample size of 104 nurses. The analysis used was univariate and bivariate analysis with the chi-square test. The results of the study showed that age (p 0.001 <0.05), length of service (p 0.000 <0.05), and workload (p 0.000 <0.05) had a relationship with work stress in nurses. Meanwhile, gender (p 0.434 > 0.05), work shift (p 0.559 < 0.05), level of work conflict (p 0.079 < 0.05), and job satisfaction (p 0.074 < 0.05) had no relationship with work stress in nurses in the inpatient ward installation at Lasinrang Regional General Hospital, Pinrang Regency in 2024. Suggestions that can be given to nurses can adjust to the workload, which must be done with the ability and capacity of nurses to avoid excessive workload and to relax to help nurses overcome stress levels.